TO DETERMINE THE RISK FACTORS FOR PREMATURE BIRTH AND EARLY DIAGNOSE THEM - Palvanova M.S (Scholar Express Journals, 2023)
We use all the information about the risk factors of premature birth or preterm birth from the online resource websites, which are PubMed, MedScape, the World Health Organization, Elsevier, and other websites. By analyzing all the data, we are able to gain an understanding of all the risk factors for premature birth, all the diagnostic methods, and the latest information about them. We hope that by clarifying that the effectiveness of various interventions aimed at reducing preterm births is not maximally beneficial, which does not reduce the rate of preterm births, early detection and diagnosis of them, rather than at the last stage, will develop measures
Keywords: premature; intact membrane; Chorioamnionitis; psychosocial stress